Esse W. Ljungh and the Winnipeg Little Theatre - Blanchard, Sharon (Theatre Research in Canada / Recherches théâtrales au Canada, 1984)
As a producer and director, as well as National Supervisor of Drama, Esse W. Ljungh was a dynamic force in the Canadian Broadcasting Corporation's radio programming during the so-called 'Golden Age'. In a study of Ljungh's activities with the Winnipeg Little Theatre in the 30s, the author of this article discovers stage roots for Ljungh's later radio drama work, as well as reveals some of the history of the Winnipeg Little Theatre. Comme réalisateur et comme metteur en ondes Esse W. Ljungh a exercé une influence puissante sur la programmation de la chaîne anglaise de Radio-Canada, à l'époque de l''âge d'or' de la CBC. En retraçant l'apport de Ljungh aux activités du Winnipeg Little Theatre au cours des années 1930, l'auteur démontre les sources théâtrales de sa contribution radiophonique, signalant en même temps des aspects mal connus de l'histoire de ce Théâtre à Winnipeg.